Group of Native men, probably Eskimos, Karluk Village, Alaska, June 1906 - Cobb, John N. (John Nathan), 1868-1930 (1906)
From John Cobb field notebook: Karluk Village, Alaska, June 1906. Shows barabara, or sod hut, in the background.